2006
DOI: 10.1901/jaba.2006.02-05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training, Prompting, and Self‐monitoring on Staff Behavior in a Classroom for Students With Disabilities

Abstract: This study extended the limited research on the utility of tactile prompts and examined the effects of a treatment package on implementation of a token economy by instructional assistants in a classroom for students with disabilities. During baseline, we measured how accurately the assistants implemented a classroom token economy based on the routine training they had received through the school system. Baseline was followed by brief in-service training, which resulted in no improvement of token-economy implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 7 publications
2
42
0
Order By: Relevance
“…These features differentiate BST from more traditional approaches to staff training in human service agencies that emphasize verbal teaching strategies such as vocal and written instructions (Parsons et al). In contrast to the noted effectiveness of BST (see Reid, O'Kane, & Macurik, 2011, for a review), investigations have repeatedly demonstrated the lack of effectiveness of the latter approaches for training staff to perform target skills (Alavosius & Sulzer-Azaroff, 1990;Gardner, 1972;Petscher & Bailey, 2006).…”
mentioning
confidence: 99%
“…These features differentiate BST from more traditional approaches to staff training in human service agencies that emphasize verbal teaching strategies such as vocal and written instructions (Parsons et al). In contrast to the noted effectiveness of BST (see Reid, O'Kane, & Macurik, 2011, for a review), investigations have repeatedly demonstrated the lack of effectiveness of the latter approaches for training staff to perform target skills (Alavosius & Sulzer-Azaroff, 1990;Gardner, 1972;Petscher & Bailey, 2006).…”
mentioning
confidence: 99%
“…The most common training formats that have shown positive training outcomes include: (a) some form of didactic instruction, such as direct instruction, (b) modeling, (c) rehearsal, and (d) feedback (Bolton & Mayer, 2008;Brock & Carter, 2013;Feldman & Matos, 2013;McCulloch & Noonan, 2013). In addition, prompting strategies (e.g., Petscher & Bailey, 2006), coaching (e.g., Duchaine, Jolivette, & Fredrick, 2011), self-monitoring (e.g., Kalis, Vannest, & Parker, 2007), and performance feedback (e.g., Reinke, Lewis-Palmer, & Merrell, 2008) have been used to enhance paraeducator use of various instructional techniques. Didactic instruction, when combined with feedback, has shown more positive outcomes in use and maintenance of skills (e.g., Koegel, Kim, & Koegel, 2014) than when used in isolation (e.g., Matthews & Hagopian, 2014).…”
Section: Type and Purpose Of Trainingmentioning
confidence: 99%
“…As such, teachers may need to consider other strategies to support students who have not responded to universal strategies. Strategies may include self-monitoring techniques (Petscher & Bailey, 2006), targeted intervention approaches such as Check in-Check out (Todd, Campbell, Meyer, & Horner, 2008), and systematic specialized intervention such as Priming (Koegel, Koegel, Frea, & Green-Hopkins, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Before implementing classroom behavioral supports, teachers should identify and evaluate existing classroom structures (Sayeski & Brown, 2011). Then develop individualized interventions for those student behaviors that require more support besides the universal classroom rules and consequences that may be sufficient to support some students (Petscher & Bailey, 2006). However, rather than approach the development of interventions using a trial-and-error approach, researchers advocate using the functional behavioral assessment (FBA) process to determine variables associated with problem behavior (Chandler& Dahlquist, 2010;Kern & Clemens, 2007;Walker, Shea, & Bauer, 2007;Zirpoli & Melloy, 1997).…”
Section: Introductionmentioning
confidence: 99%